COMPARATIVE CHARACTERISTICS OF IVF PROGRAMS EFFECTIVENESS IN PATIENTS WITH ADENOMYOSIS AND TUBAL-PERITONEAL INFERTILITY - SudomaI.А. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
Standardization of IVF cycles and ignoring of peculiarities of diseases, which leads to infertility could be the cause of low effectiveness of treatment. The aim of this work was to investigate and compare the results of IVF programs of the patients with adenomyosis and tubal-peritoneal infertility. The results of 202 IVF cycles in 136 patients with adenomyosis (main group – MG) and 92 cycles in 68 patients with tubal-peritoneal infertility (group of comparison CG) were analyzed in relation to cycle quantity,age, embryo quantity. Pregnancy rate was significantly lower in MG in comparison to CG (14,8% and 26,1% ), especially low effectiveness was seen in patients with adenomyosis and endometriosis (8,5%). Most of pregnancies were achieved after first two cycles on MG and CG (90% и 83,3%) and with young women (around 90%). The best results in MG were achieved after transfer of not more than three embryos and in CG – after transfer from three to six embryos. The analysis of IVF programs in patients with adenomyosis shows that the reproductive capacities of these women are worse if compared with patients with tubal-peritoneal infertility. In IVF programs of these patients such peculiarities must be taken into account: not more than two standard IVF programs must be fulfilled, not more than three embryos have to be transferred, after two IVF failures the more accurate diagnosis must be provided to reveal the factors which interfere with achieving pregnancy.